HUBUNGAN PELAYANAN TENAGA KESEHATAN DAN SARANA PRASARANA SERTA TARIF PUSKESMAS DENGAN PUBLIC DEMAND DALAM PELAYANAN KESEHATANDI WILAYAH PUSKESMAS LABUHAN RASOKI KOTA PADANGSIDIMPUAN TAHUN 2020 - Amir Hamsah Siregar (Jurnal Kajian Kesehatan Masyarakat, 2020)
Community health center is a strategic unit in supporting the realization of changes in public health status to have improving optimal health status. To realize optimal health status, an effort to develop a basic health service system that is able to fulfil the needs of the community as consumers of these basic health services, in addition to the first level health facilities that carry out Public Health Efforts (PHE), and Individual Health Efforts (IHE) with prioritizing promotive and preventive efforts to achieve the highest degree of public health in the working area of Labuhan Rasoki Community Health Center, Padangsidimpuan City (health ministy roly, 2017). According to the World Health Organization (WHO) in 2014, the number of people using health services in India was 60.4 million, in China 985 million were using health services, while in other parts of Asia it was 38.4 million people are still lacking in utilizing services. The purpose of this study was to analyze the relationship between health service personnel, facilities and infrastructure, as well as Public Health Center ,rates with public demand in health services in the Rasoki harbor area in 2020. This study is a quantitative research with cross sectional approach with a total sample of 86 Non the national health assurance community patients. The study instrument was questionnaire and data analysis was performed using logistic regression tests at the real level α = 0.05. The results of the analysis in this study found a significant relationship between service of health workers (p = 0.001), facilities and infrastructure (p = 0.003), Public health center rates (p = 0.013) and public demand in health services in the Labuhan Rasoki port area of the city of Padangsidimpuan in 2020. It is recommended to the Public health center so that it can increase the role of health workers in serving patients.